2021
DOI: 10.1002/cpe.6802
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 detection with severity level analysis using the deep features, and wrapper‐based selection of ranked features

Abstract: The SARS-COV-2 virus, which causes COVID-19 disease, continues to threaten the whole world with its mutations. Many methods developed for COVID-19 detection are validated on the data sets generally including severe forms of the disease.Since the severe forms of the disease have prominent signatures on X-ray images, the performance to be achieved is high. To slow the spread of the disease, effective computer-assisted screening tools with the ability to detect the mild and the moderate forms of the disease that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The experimental results on a hold-out set demonstrate that classification with the selected Xception network features yields good generalization ability. 7 Ramazan It has been observed that the proposed pipeline is a promising solution to reducing FP cases. 8 The guest editors hope that the research contributions and findings in this special issue would benefit the readers in enhancing their knowledge and encouraging them to work on various aspects of intelligent systems and applications.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results on a hold-out set demonstrate that classification with the selected Xception network features yields good generalization ability. 7 Ramazan It has been observed that the proposed pipeline is a promising solution to reducing FP cases. 8 The guest editors hope that the research contributions and findings in this special issue would benefit the readers in enhancing their knowledge and encouraging them to work on various aspects of intelligent systems and applications.…”
Section: Editorialmentioning
confidence: 99%
“…Proposed method is cross‐validated on a challenging data set containing all the forms of COVID‐19 disease. The experimental results on a hold‐out set demonstrate that classification with the selected Xception network features yields good generalization ability 7 …”
mentioning
confidence: 92%